Intragenic β-synuclein rearrangements in malignancy - Xiao, Peifang; Chen, Nan; Shao, Tingting; Bian, Xinni; Miao, Jie; Zheng, Jiajia; Lang, Xingping; Wang, Yiting; Chen, Xiaojun; Jin, Liqin; Hu, Shaoyan; Xiao, Sheng (Frontiers in Oncology, 2023)
The synuclein family, consisting of α-, β-, and γ-synuclein, is primarily expressed in neurons. Mutations of α- and β-synuclein have been linked to Parkinson's disease and dementia with Lewy bodies, respectively. Recent studies have shown that synucleins are upregulated in various tumors, including breast, ovarian, meningioma, and melanoma, and high synuclein expression is associated with poor prognosis and drug resistance. We report a novel rearrangement of β-synuclein in a pediatric T-cell acute lymphoblastic leukemia (T-ALL) case, where β-synuclein (SNCB) is fused in-frame with ETS variant transcription factor 6 (ETV6), a gene frequently rearranged in acute leukemia including acute myeloid leukemia (AML), B-cell acute lymphoblastic leukemia (B-ALL), and T-ALL. An additional case of β-synuclein rearrangement was identified in a squamous cell carcinoma of the lung through analysis of the public TCGA database. Both rearrangements involve the C-terminal of β-synuclein. Since β-synuclein shares extensive amino acid similarities with α-synuclein and α-synuclein binds to 14-3-3, an important regulator of apoptosis, the rearranged β-synuclein may contribute to tumorigenesis by deregulating apoptosis. In addition, overexpression of synucleins has been shown to increase cell proliferation, suggesting that the rearranged β-synuclein may also deregulate the cell cycle.